Feldman M.G. Estimation of the number of sockeye salmon adults and their distribution by spawning stations in the basin of Lake Nachikinskoye (Kamchatka) in 2019 - G. V. Zaporozhets; O. M. Zaporozhets; M. G. Feldman (Известия ТИНРО, 2020)
Data on quantitative distribution of early and late spawners of sockeye salmon in the Lake Nachikinskoye basin were collected in 2019 using quadcopter. Features of sockeye spawning in certain sectors of the lake coast and at the spawning stations are analyzed. The spawning starts earlier on the eastern coast, and then on the western coast. The late sockeye spawning is considered in details at the spawning stations on littoral shelves, on steep coastal slopes, in key limnocrenes, in algae fields at the depths up to 5 m, and in the river tributaries. Environmental conditions of the stations are compared quantitatively by several parameters, as water flows and their gradients, water temperature, dissolved oxygen content, soils composition, impact of predators and waves. Each station has its advantages and disadvantages. The lake shallows dominate among the spawning grounds, but their diversity provides stability and even growth of local sockeye salmon stocks. Spatial distribution of the sockeye spawning grounds is described. The number of spawned fish is assessed using the trapezoid approximation (TAUC) as 55 . 103 ind. for early sockeye and 132 . 103 ind. for late sockeye that shows a considerable growth of the stocks of sockeye salmon in Lake Nachikinskoye since the middle of last century.